Achieving Business Continuity through Succession Planning among Small & Medium Enterprises in the Food and Beverage Industry - Kong, Michele Suet Mei (2015)
Succession planning plays a key role in ensuring the long-term continuity of a business. Evidence has shown that only a very small percentage of family-owned businesses continue to the third generation and succession planning is not given sufficient weight in such businesses. As research has shown that a poor (or poorly executed) plan for succession can seriously destabilize a business, it is imperative that more is done to ensure that such businesses are aware of the need for succession planning and the factors they have to consider in doing so. Employing a narrative analysis as a research design, this paper aims to explore the views and concerns of family owned small and medium sized food and beverage enterprises in planning for their long term future, with added weight on their plans for succession of their businesses. This paper aims to create more awareness of the challenges faced by these business owners in planning for the succession of their businesses.